AB1120 Comparison of Long-Term Drug Survival of Tumor Necrosis Factor Inhibitors in Patients with Rheumatoid Arthritis, Ankylosing Spondylitis and Psoriatic Arthritis: A Single Center Turkish Experience Over a Decade. (9th June 2015) - Can, G.; Capar, S.; Cetin, P.; Solmaz, D.; Kenar, G.; Yarkan, H.; Akar, S.; Birlik, M.; Sari, I.; Onen, F.; Akkoc, N.
Abstract : Background: The studies from different national biologics registries provide data on long term efficacy and safety of tumor necrosis factor inhibitors inhibitors (TNFi) for the treatment of rheumatic diseases in diverse patient populations. The data in this regard is lacking in Turkish population. Objectives: To assess and compare the long term drug survival rates of TNFi in patients with rheumatoid arthritis (RA), ankylosing spondylitis (AS) and psoriatic Arthritis (PsA) and to identify potential reasons for treatment discontinuation. Methods: The analysis included all the patients treated with TNFi at our center since 2004. Persistence on anti-TNF in patients who were lost to follow-up were analyzed using the national prescription database. Patients with no prescription over the last 6 months were considered to have discontinued the treatment. The date of the last prescription was accepted as the date of discontinuation. These patients were tried to be contacted by phone to identify the reason for discontinuation. Kaplan-Meier plots and log rank tests were used to assess drug survival. Results: Of the 351 patients in the study 222 had AS (26.1% females, mean age: 44.3±11.7 years, mean disease duration: 20±9.9 years, HLA-B27:(+): 71.1%), 96 had RA (78.2% females, mean age: 53±13.9 years, mean disease duration: 15.1±7.7 years, RF (+): 59.1%, anti-CCP (+): 67.9%) and 32 had PsA (62.2% females, mean age: 47±14.2, mean disease duration: 12.2±8.7). Etanercept (ETA) was started in 123 (35.1%) patients, infliximab in 116 (33.1%), adalimumab (ADA) in 98 (28%) and golimumab (GOL) in 13 (%3, 7). Over an observational period of up to 10 years, biologic treatment was discontinued in 198 (56.4%) patients, of whom 137 (69%) were switched to another TNFi. Drug survival rate for all of the three anti-TNF-α agents is 48.6% for AS, 37.5% for RA, and 40.6% for PsA. Median drug survival time in AS was 67.4 (95% CI, 58.5-76.3) and seemed to be longer than in RA (51.6 months, 95%CI 37.8-65.4) and PsA (45.5 months, 95% CI 30.0-61.0). No difference was observed between different TNFi within the same disease category. In patients with RA, female patiens had a longer drug survival than male patients. The reasons for discontinuation were inefficacy in 86 patients (44.3%), adverse events in 45 (23.2%) (tuberculosis in 2 patients, malignancy in 4 patients), remission in 10 (5.2%) and other or unclear reasons in 55 (29.3%). During the observational period four patients died, one due to lymphoma which developed during anti-TNF therapy, one due to metastatic germ cell tumor which developed one year after the cessation of antiTNF therapy, two due to possibly not related to the anti-TNF therapy. Conclusions: Our single center study indicate generally similar long term drug survival rates for TNFi within a disease category. The trend for a better long term drug survival in this study is in line with some previously published. Disclosure of Interest: G. Can: None declared, S. Capar: None declared, P. Cetin: None declared, D. Solmaz: None declared, G. Kenar: None declared, H. Yarkan: None declared, S. Akar: None declared, M. Birlik: None declared, I. Sari: None declared, F. Onen: None declared, N. Akkoc Grant/research support from: Pfizer UCB, Consultant for: Pfizer UCB Abbvie MSD BMS, Speakers bureau: Pfizer UCB Abbvie MSD